The Investigation on Initiation and Propagation of Hydraulic Fractures in Shale Reservoir. (27th November 2021) - Liu, Xiangjun; Lei, Wei; Huang, Jing; Ding, Yi; Liang, Lixi; Xiong, Jian
Abstract : Hydraulic fracturing is a necessary technique for shale gas exploitation. In order to have efficient stimulation treatment, a complex fracture network has to be developed, whereas with rich bedding planes and natural fractures, the mechanism of forming a fracture network is not fully understood and it is so tricky to predict propagation and initiation of hydraulic fracture. Therefore, in this paper, considering the strong anisotropy of shale reservoir, numerical simulation has been conducted to analyze fracture propagation and initiation on the basis of finite element and damage mechanics. Simulation results indicate that hydraulic fracture is not merely controlled by in situ stress due to strong anisotropy in shale. With plenty of bedding planes, hydraulic fracture tends to have initiation and propagation along the bedding plane. In particular, this influence becomes stronger with low strength and high development density of bedding planes. Additionally, in combination with natural fracture and bedding plane, the initiation point is usually on a natural fracture plane, causing relatively small breakdown pressure. In the process of fracture propagation, hydraulic fracture connects with natural fractures and bedding planes, forming dendritic bifurcation and more complicated paths. Numerical simulation proves that bedding plane and natural fracture are vital factors of hydraulic fracture. Compared to natural fracture, the bedding plane has a stronger impact on hydraulic fracture propagation. For the initiation of hydraulic fracture, natural fracture is the major effecting factor. The outcome of this study is able to offer theoretical guidance for hydraulic fracturing in shale.